Ibn Al-Jazzar On Sexual Diseases A critical edition of Zad al-musafir wa-qut al-hadir - Provisions for the Traveller and Nourishment for the Sedentary, Book 6 - Bos, Gerrit (The Sir Henry Wellcome Asian Series, 1997)
First published in 1997. Routledge is an imprint of Taylor & Francis, an informa company.